(untitled) (Homiletic, 2023)
In the mid-twentieth century, New York City experienced a renaissance of Protestant preaching. William B. Lawrence identifies four preachers who won acclaim: Harry Emerson Fosdick, Ralph Sockman, George A. Buttrick, and Paul W. Scherer. Lawrence argues rightly that these preachers were popular and influential; however, his research delimits the renaissance to white Mainline ministers. Preachers from minoritized churches also maintained vibrant preaching ministries in the city. In this paper, I consider the ministries of Adam Clayton Powell Jr., Sandy F. Ray, and Gardner C. Taylor, three black Baptist pastors that ministered in “East” New York, to expand the contributions to preaching’s renaissance in the city as well as bring their stories closer to the center of homiletical-historical inquiry.